Representation of Alternative Masculinity in Tere Liye’s Novel "Janji" - Annisa Nurhikmah; Alfian Rokhmansyah (JENTERA: Jurnal Kajian Sastra, 2026)
This research aims to examine in depth the construction of alternative masculinity in Tere Liye’s novel Janji through a sociology of literature perspective, which examines the reciprocal relationship between literature and social reality. This study employs a descriptive qualitative approach. The research data consist of words, phrases, and sentences representing gender elements, with the primary data source being the text of the novel Janji (2021). Data were collected through a literature review and note-taking techniques, followed by in-depth textual analysis to dissect the social dimensions within the text. Data analysis used the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The results show that the main character, Bahar, represents an alternative masculinity that prioritizes empathy, social solidarity, and moral responsibility, while simultaneously deconstructing the dominance of hegemonic masculinity, typically associated with violence and dominance. The implications of this research contribute to the development of gender studies in Indonesian literature and offer new perspectives in literary education regarding the dynamic nature of gender construction. By applying Connell’s masculinity theory, this research proves that the figure of Bahar represents an alternative masculinity model relevant for integration as progressive Indonesian language and literature learning materials. Abstrak Penelitian ini bertujuan untuk mengkaji secara mendalam konstruksi maskulinitas alternatif dalam novel Janji karya Tere Liye melalui perspektif sosiologi sastra yang meneliti hubungan timbal balik antara sastra dan realitas sosial. Studi ini menggunakan pendekatan kualitatif deskriptif. Data penelitian terdiri dari kata, frasa, dan kalimat yang mewakili unsur gender, dengan sumber data utama berupa teks novel Janji (2021). Data dikumpulkan melalui teknik tinjauan pustaka dan pencatatan, diikuti dengan analisis tekstual mendalam untuk membedah dimensi sosial dalam teks. Analisis data menggunakan model Miles dan Huberman, yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa tokoh utama, Bahar, mewakili maskulinitas alternatif yang memprioritaskan empati, solidaritas sosial, dan tanggung jawab moral, sekaligus mendekonstruksi dominasi maskulinitas hegemonik yang biasanya dikaitkan dengan kekerasan dan dominasi. Implikasi penelitian ini berkontribusi pada pengembangan studi gender dalam sastra Indonesia dan menawarkan perspektif baru dalam pendidikan sastra mengenai sifat dinamis konstruksi gender. Dengan menerapkan teori maskulinitas Connell, penelitian ini membuktikan bahwa figur Bahar mewakili model maskulinitas alternatif yang relevan untuk diintegrasikan sebagai bahan pembelajaran bahasa dan sastra Indonesia yang progresif.